Perception of Tax Center Services as a Determinant of Satisfaction - Destiana, Destiana; Jufri Yandes; Jasrial; Syarif Fadillah; Husna Puteri P; Syafiqoh Nurhayati; Dedy Juaniadi; Aji Fajar Suryo Antoro; Muhtarom; Dwi Rahmawati; Laras Ayu Andini; Ridha Azka Raga (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2025)
Tax revenue is the main source of state revenue and to achieve its growth, effective service is needed to increase taxpayer satisfaction. This study aims to provide the impact of Tax Center services on taxpayer satisfaction in the context of the Open University. Using a quantitative descriptive method, data were collected from 115 respondents consisting of lecturers and education staff through a structured questionnaire. The questionnaire measured five dimensions of service, namely physical evidence, transmission, responsiveness, assurance, and empathy, and overall with satisfaction analyzed using the SmartPLS 4.0 application. The results of the study indicate that although empathy has a significant effect on taxpayer satisfaction, other dimensions, namely physical evidence, income, responsiveness, and assurance, do not show a significant effect. Empathy, which includes attention to taxpayer needs, problem solving, and ease of service, is identified as the strongest determinant of satisfaction. This study underlines the importance of empathetic involvement by Tax Center officers in assisting taxpayers, especially in reporting SPT, which increases overall satisfaction. Conversely, other dimensions of impact that are not significant indicate the need for improvement in service delivery. This study concludes with recommendations to strengthen service quality in all dimensions to improve taxpayer satisfaction and compliance.